دراسة مقارنة لنتائج تعلم اللغة العربية بين المنهج 13 ومنهج ميرديكا في ديلي سردانج - Saddiah, Saddiah; Zaky, Ahmad; Ulum, Bahrul (Lembaga Yasin AlSys, 2025)
This research investigates the differences in Arabic language learning outcomes between students following Curriculum 13 at State Senior High School 2 Deli Serdang and those following the Merdeka Curriculum at State Senior High School 1 Deli Serdang. It aims to determine whether there are statistically significant differences between the two groups. The researcher employed a quantitative method using the ex post facto approach. A sample of 60 students was selected through simple random sampling, with 30 students from each school. Data were collected using an achievement test on the topic of